The Influence of Service Quality on Visitor Satisfaction at Tiban Global Night Market Shopping Tourism in Batam - Lapotulo, Nensi; Afriani, Miratia; Sukmamedian, Haufi; Saputra, Eryd (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This research is based on shopping tourism that is currently growing, where visitor satisfaction is a climax of shopping tourism that provided service quality. This research aims to find out the influence of service quality on visitor satisfaction at Tiban Global night market as a shopping tourism located in Batam City of Indonesia, by using quantitative methods. The respondents taken in this study were 76 respondents. The data analysis techniques used are classical assumption tests, partial hypothesis tests and determination coefficient (R2) tests. While the data used in the study is primary data with questionnaire filling which is shared directly with visitors. The results of this study found that data processed by statistical means showed service quality variables with indicators, physical evidence, responsiveness, reliability, assurance and empathy had a significant influence on visitor satisfaction variables where t-count values of 9,247 and t-tabels of 1,993 (9,247>1,993) and significant values of service quality of 0,000<0.05 which means H0 was rejected and Ha accepted. The research analyzed data found that reliability is the most positively responded indicator of service quality. Conformity to expectations is the most positively responded indicator of visitor satisfaction. Service quality significantly influences visitor satisfaction, as the t-count value is greater than the t-table value. The determinant coefficient test revealed that service quality has a significant influence on visitor satisfaction, with an R2 value of 53.6%. The research concludes that service quality has a significant impact on visitor satisfaction at the Tiban Global night market, but there are still other independent variables not examined in this study that influence the remaining 56.4% of visitor satisfaction.